Import competition and local labor markets: the case of Indonesia - Agustina, Fina Sri (Economic Journal of Emerging Markets, 2018)
This paper analyzes the effects of import competition on Indonesian local labor markets in term of manufacturing employment share, non-manufacturing employment share, unemployment rate, and wages. A rapid increase of globalization has caused many countries including Indonesia experienced a significant increase in imports, which lead to a tougher import competition. Using data of imports and 430 districts in Indonesia in the period of 2007-2013, we found that import competition has negatively affected manufacturing employment share, non-manufacturing employment share, and wages. It also increased unemployment. In addition, the highest impact was mainly driven by imports of consumption goods